Widows [videorecording (DVD)] - McQueen, Steve, 1969-; Davis, Viola, 1965-; Rodriguez, Michelle; Debicki, Elizabeth; Farrell, Colin, 1976-; Duvall, Robert; Neeson, Liam; La Plante, Lynda (Twentieth Century Fox Home Entertainment, 2019)
Four women with nothing in common except a debt left by their dead husbands' criminal acts conspire to take fate into their own hands.